2018
DOI: 10.1037/per0000256
|View full text |Cite
|
Sign up to set email alerts
|

Mentalizing as a mechanism of change in the treatment of patients with borderline personality disorder: A parallel process growth modeling approach.

Abstract: Although a number of effective psychotherapeutic treatments have been developed for borderline personality disorder (BPD), little is known about the mechanisms of change explaining the effects of these treatments. There is increasing evidence that impairments in mentalizing or reflective functioning-the capacity to reflect on the internal mental states of the self and others-are a central feature of BPD. To date, no study has directly investigated the core assumption of the mentalization-based approach to BPD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 32 publications
8
59
1
6
Order By: Relevance
“…Of course, we cannot rule out the hypothesis that overall metacognition simply does not act as a mechanism of change, as our main finding nuances De Meulemeester et al . 's () study where a strong association was found between improvement in mentalizing and symptom change during treatment. Part of that difference could be explained by the nature of the method used, in addition to conceptual divergence of how the potential mechanism of change was defined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of course, we cannot rule out the hypothesis that overall metacognition simply does not act as a mechanism of change, as our main finding nuances De Meulemeester et al . 's () study where a strong association was found between improvement in mentalizing and symptom change during treatment. Part of that difference could be explained by the nature of the method used, in addition to conceptual divergence of how the potential mechanism of change was defined.…”
Section: Discussionmentioning
confidence: 97%
“…Changes in reflective functioning were negatively linked with changes in personality organization. Recently, De Meulemeester, Vansteelandt, Luyten, and Lowyck () examined mentalization as a predictor and as a mechanism of change in a long‐term hospitalization‐based psychodynamic treatment for BPD patients. Levels of mentalization at onset did not predict symptom change but a strong correlation was observed between change in symptomatic distress and change in uncertainty about mental states.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the clinical issues outlined, it is essential not only to go beyond the mere demonstration of outcome in psychotherapy, but also to improve our understanding of the underlying processes at work in treatment (Clarkin, 2014;Kramer, 2019) by conducting psychotherapy studies similar to those that have addressed borderline personality disorder (De Meulemeester, Vansteelandt, Luyten, & Lowyck, 2018;Fonagy & Bateman, 2006;Gratz, Bardeen, Levy, Dixon-Gordon, & Tull, 2015;Levy et al, 2006). At the present time, the mechanisms of changes in NPD are insufficiently understood.…”
Section: Mechanisms Of Change: Theoretical Considerations and Empiricmentioning
confidence: 99%
“…Levy and colleagues (2006) examined change in three forms of psychotherapy for BPD --TFP, DBT and supportive therapy -and found that only TFP was associated with an increase in mentalizing functions, along with development of more secure attachment patterns in some patients in this group [29]. Consistent results were presented by Fischer-Kern and colleagues [61] (see also de Meulemeester et al [62]; Maillard et al, [63]). Other research has underlined the moderating factor of mentalizing capacities for outcome for different categories of PD [64,65].…”
Section: Mechanisms Of Change In Treatments For Borderline Personalitmentioning
confidence: 70%